A second species of the orb-weaving spider genus Melychiopharis from South America (Araneae: Araneidae) - Brescovit, Antonio D.; Santos, Adalberto J.; Leite, Clarissa Machado P. (Zootaxa, 2011)
The genus Melychiopharis Simon was originally described in the family Araneidae, placed close to Hypognatha Guérin-Méneville (Simon 1895: 907). Levi (2002) transferred the genus to Theridiidae, based on its unusual morphology, which is extremely different from the araneid body plan. However, Santos et al. (2005) presented evidence suggesting that this genus is closer to araneid genera, like Hypognatha and Testudinaria Taczanowski and, consequently, transferred it back to Araneidae. That study also included a redescription and illustrations of the genus and of its only species, M. cynips Simon, 1895, which is currently known from northern, central and northeastern Brazil.